Performance of Automatic Temperature Control System in Pyrolysis Reactor of LDPE Plastic Waste - Putrawan, I Made Agus; Susila, I Nengah Darma; Suparta, I Nyoman (invotek, 2023)
Pyrolysis is a process of decomposing material at high temperatures without or with limited air and is an alternative waste treatment which is considered quite prospective to be developed. Plastic waste treatment as pyrolysis fuel, is strongly influenced by operating conditions, which consist of the thermal properties of plastics such as the LDPE type, which are still massively used in society. This research processes LDPE type plastic waste using technology fixed bed pyrolysis type batch reactor with a capacity of 0.01 m³ with initial heating from external heat of LPG energy source. The pyrolysis process takes in a closed reactor and the mass flow rate of the condensate flows naturally to the condenser for the condensation process to become pyro-oil product. Optimization of the reactor pyrolysis was carried out by adding insulated heat cover to reduce heat losses during the heating process. The addition of automatic temperature control to regulate the heating rate, makes operation control easier and reducing fluctuations in temperature distribution during pyrolysis process. The research was carried out with three operating temperature variations of 250, 275, and 300 °C using 0.8 kg LDPE plastic waste for batch test. The performance of automatic temperature control was observed using a digital thermometer and a comparison of the results before and after installation was carried out at a temperature of 300 °C. The results showed that heating temperature control which was previously done manually gives fluctuating results with a temperature difference of up to 50 °C. With the addition of an automatic temperature control system, the operating temperature during the pyrolysis process shows relatively lower fluctuations with a maximum difference of 20 °C. The initial heating energy consumption from LPG and the fuel consumption rate (FCR) show an increase along with the increase in the pyrolysis operating temperature setting.